1991
DOI: 10.1007/bf03347907
|View full text |Cite
|
Sign up to set email alerts
|

Increased mean serum thyrotropin in apparently euthyroid hypercholesterolemic patients: does it mean occult hypothyroidism?

Abstract: Serum thyroid hormones and antithyroid autoantibodies (AAB) were assayed in 87 randomly selected hypercholesterolemic persons compared to 80 controls with normal serum total cholesterol (TC). Of the 87 hypercholesterolemic persons 22 (25%) had positive AAB compared to 5 (6%) controls. Furthermore, 8 of the hypercholesterolemic patients had a serum TSH level above 5 mU/l, i.e. the had subclinical hypothyroidism, not diagnosed before, whereas thyroid function was normal in all normocholesterolemic persons. The n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 16 publications
2
23
0
1
Order By: Relevance
“…We had previously observed that almost 10% of asymptomatic hypercholesterolemic patients have in fact subclinical hypothyroidism (9); in that study we had also observed that even TSH levels in the upper normal range may be associated with lipid abnormalities (9).…”
Section: Introductionmentioning
confidence: 59%
“…We had previously observed that almost 10% of asymptomatic hypercholesterolemic patients have in fact subclinical hypothyroidism (9); in that study we had also observed that even TSH levels in the upper normal range may be associated with lipid abnormalities (9).…”
Section: Introductionmentioning
confidence: 59%
“…It has been reported that subjects with high-normal serum TSH levels (2.1 -4.0 AIU/ml) frequently present hypercholesterolemia [27] and also have a tendency to develop overt hypothyroidism later in their life [28]. Moreover, subjects with TSH values at the upper normal limits, present augmentation of the central arterial pressure by wave reflection, resulting from systematic arterial stiffening [29].…”
Section: Discussionmentioning
confidence: 98%
“…In Groups 0 and 1, thyroid antibodies titers were negative. TSH values in the lower end of the spectrum (0.3 -4.0 AU/ml) were viewed as two separate groups (0.3 -2 and 2 -4 AU/ml) based on recent reports suggesting readjustment of normal TSH values to lower levels and on our own previously published data suggesting that upper normal TSH range may in fact represent early stages of subclinical hypothyroidism [15,27,30].…”
Section: Methodsmentioning
confidence: 99%
“…Overt hypothyroidism is a risk factor for renal dysfunction in the general population, and thyroid replacement therapy is effective for preventing a progression of renal dysfunction in addition to improving dyslipidemia [21]. In a sample of female Japanese participants, low-density lipoprotein cholesterol and triglyceride levels were higher in patients with SCH [31], and thyroid replacement therapy reduced both total and low-density lipoprotein cholesterol levels among patients with SCH [32,33]. However, the effectiveness of thyroid replacement therapy for SCH to prevent renal dysfunction remains unclear.…”
Section: Discussionmentioning
confidence: 99%